QTL for seed iron and zinc concentration and content in a Mesoamerican common bean (Phaseolus vulgaris L.) population - Blair, Matthew W.; Medina, JI; Astudillo, Carolina; Rengifo Medina, J; Beebe, Stephen E.; Machado, G; Graham, RD (Springer, 2010)
Iron and zinc deficiencies are human health problems found throughout the world and biofortification is a plant breeding-based strategy to improve the staple crops that could address these dietary constraints. Common bean is an important legume crop with two major genepools that has been the focus of genetic improvement for seed micronutrient levels. The objective of this study was to evaluate the inheritance of seed iron and zinc concentrations and contents in an intra-genepool Mesoamerican × Mesoamerican recombinant inbred line population grown over three sites in Colombia and to identify quantitative trait loci (QTL) for each mineral. The population had 110 lines and was derived from a high-seed iron and zinc climbing bean genotype (G14519) crossed with a low-mineral Carioca-type, prostrate bush bean genotype (G4825). The genetic map for QTL analysis was created from SSR and RAPD markers covering all 11 chromosomes of the common bean genome. A set of across-site, overlapping iron and zinc QTL was discovered on linkage group b06 suggesting a possibly pleiotropic locus and common physiology for mineral uptake or loading. Other QTL for mineral concentration or content were found on linkage groups b02, b03, b04, b07, b08 and b11 and together with the b06 cluster were mostly novel compared to loci found in previous studies of the Andean genepool or inter-genepool crosses. The discovery of an important new locus for seed iron and zinc concentrations may facilitate crop improvement and biofortification using the high-mineral genotype especially within the Mesoamerican genepool.